Efficient energy consumption in industrial sectors and its effect on environment: A comparative analysis between G8 and Southeast Asian emerging economies - Rahman, Md. Saifur; Md. Noman, Abu Hanifa; Shahari, Farihana; Aslam, Mohamed; Chan, Sok Gee; Isa, Che Ruhana; Pervin, Sajeda (2016)
This study investigates the long-term relationship between industrial production and energy consumption along with the environmental degradation in developed and developing countries. The purpose of this study is to identify countries that meet the competitive challenges of achieving efficient environmentally friendly energy consumption. The investigation process utilises the Toda Yamamoto technique looking at 40 years of data from 1971 to 2011. The investigation reveals that both G8 and Southeast Asian countries are energy dependent, as indicated by unidirectional Granger causality running from energy consumption to industrial production. The most energy efficient economies are among G8 countries and the least efficient are found in Southeast Asian countries. The results also reveal that industrial production of developed countries is more environmentally friendly than developing countries. Finally, the study provides significant policy implications toward improving energy security and efficiency.